2015
DOI: 10.1016/j.tim.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus infections: transmission within households and the community

Abstract: Staphylococcus aureus , both methicillin susceptible and resistant, are now major community-based pathogens worldwide. The basis for this is multifactorial and includes the emergence of epidemic clones with enhanced virulence, antibiotic resistance, colonization potential, or transmissibility. Household reservoirs of these unique strains are crucial to their success as community-based pathogens. Staphylococci become resident in households, either as colonizers or environmental contaminants, increasing the risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
107
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(117 citation statements)
references
References 102 publications
5
107
0
5
Order By: Relevance
“…Among the foodborne disease-causing bacteria involved in predominant foodborne disease outbreaks, Staphylococcus aureus is one of the leading causes of gastroenteritis resulting from the consumption of contaminated food [1]. Since 2010 in South Korea, approximately 1,180 people have been hospitalized from 66 outbreaks of Staphylococcus [2].…”
Section: Introductionmentioning
confidence: 99%
“…Among the foodborne disease-causing bacteria involved in predominant foodborne disease outbreaks, Staphylococcus aureus is one of the leading causes of gastroenteritis resulting from the consumption of contaminated food [1]. Since 2010 in South Korea, approximately 1,180 people have been hospitalized from 66 outbreaks of Staphylococcus [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, new strains of S. aureus that have acquired further virulence factors and toxins or that have adapted to a specific environment, for example, an increased ability to cause bacteremia (2), are still a considerable threat. There is now widespread community-associated methicillin-resistant S. aureus (CA-MRSA), and infections can spread within households, day care centers, and schools (3). In addition, Giuffre et al observed an increasing incidence of MRSA in neonates (4).…”
mentioning
confidence: 99%
“…Theoretically, these nasal MRSA carriers can serve as a reservoir for MRSA transmission to others and be exposed to self‐contamination with MRSA. Especially, MRSA carriers are known to transmit MRSA to household members and to increase the risk of recurrent infections among individuals who are in close contact in the community as well as in their households.…”
Section: Discussionmentioning
confidence: 99%
“…Methicillin‐resistant Staphylococcus aureus (MRSA) has been considered a pathogen of great concern because of the burden of serious disease associated with infection. In addition to relatively mild skin and soft‐tissue infections, MRSA can cause life‐threatening pneumonia and sepsis. The prevalence of MRSA differs considerably among regions and countries.…”
Section: Introductionmentioning
confidence: 99%